Delivery of a drug cache to glioma cells overexpressing platelet-derived growth factor receptor using lipid nanocarriers. (March 2016) - Miller, Kayla; Dixit, Suraj; Bredlau, Amy-Lee; Moore, Alfred; McKinnon, Emilie; Broome, Ann-Marie
Aim: Glioblastoma multiforme is a devastating disease with no curative options due to the difficulty in achieving sufficient quantities of effective chemotherapies into the tumor past the blood–brain barrier. Micelles loaded with temozolomide (TMZ) were designed to increase the delivery of this drug into the brain.Materials & methods: pH-responsive micelles composed of distearoyl phosphoethanolamine-PEG-2000-amine and N-palmitoyl homocysteine were surface-functionalized with PDGF peptide and Dylight 680 fluorophore.Results & conclusion: PDGF-micelles containing TMZ have specific uptake and increased killing in glial cells compared with untargeted micelles. In vivo studies demonstrated selective accumulation of PDGF-micelles containing TMZ in orthotopic gliomas implanted in mice. Targeted micelle-based drug carrier systems hold potential for delivery of a wide variety of hydrophobic drugs thereby reducing its systemic toxicity.